Late Tortonian - Piacenzian multi-proxy record of Asian southwest monsoon intensification: evidence from Coastal Makran, southeast Iran - Modarres, Mohammad Hadi; Rehfeld, Kira (Canadian journal of earth sciences, 2019)
This study presents a long-term, multi-proxy reconstruction of the Asian southwest monsoon during the Tortonian to Piacenzian, based on a 4.78 Ma record from Coastal Makran, northwestern Gulf of Oman, southeast Iran. The integration of humidity proxies (clay minerals, Th/K, volume magnetic susceptibility, and grain size analysis), marine redox sensitivity (Th/U), total organic matter, carbonate content, 87Sr/86Sr ratio, and spectral gamma-ray data conducted here provide valuable information that fill the existing gap in marine palaeoclimate records. The results show that a strong winter monsoon condition associated with relatively low precipitation and subsequently low physical and chemical weathering dominated the region during late Tortonian - late Messinian (7.65-5.83 Ma). However, a few episodes of intense physical and chemical weathering related to high precipitation are observed during this period (6.23-6.01 Ma), which is consistent with increased organic matter input from continental reservoirs to the oceans. In addition, the data indicate that from the latest Messinian (5.82-5.33 Ma) to Zanclean-Piacenzian (5.33-2.87 Ma), a strong summer monsoon accompanied by a relatively wetter condition and higher physical and chemical weathering resulted in a high detrital input into the basin. This higher weathering period is associated with the highest rate of Himalayan uplift, causing enhanced precipitation. Wavelet analysis of spectral gamma-ray data revealed notable periodicities at 750 Ka and 1.7 Ma, with significant periodicities centered around 5.75-6.03 Ma over the latest Messinian - Zanclean. Comparison with palaeoclimate records from other sites indicates a teleconnection with respect to precipitation, weathering, and productivity, especially during the Messinian-Zanclean transition.